EU powers under external pressure : how the EU's external actions alter its internal structures - Eckes, Christina (Oxford : Oxford University Press, 2019)
EU external actions have deep constitutional and institutional implications for EU law and practices. The EU's competences in external relations have continuously increased, including with the entry into force of the Treaty of Lisbon. As a result, the EU has become ever more active in external relations. This has in turn increased the internal constitutional and institutional effects of EU external actions. This text traces these legal effects and the broader constitutional implications, including potential integrative forces.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 4, 2019).
Keywords: European Union; European Union countries -- Foreign relations -- 21st century; Law; International law